Authentic Leadership, Psychological Safety, and Innovative Work Behavior: Testing a Mediation Model Among Generation Z Employees in Technology Companies - Emha Zainul Mukminin (Social Science Academic, 2026)
Background: The rapid expansion of technology companies has heightened the demand for sustained innovation, yet many organizations struggle to cultivate the psychological conditions that enable employees to take creative risks. For Generation Z workers—digital natives who seek meaning, autonomy, and authenticity at work—the quality of leadership may be particularly consequential in shaping these conditions. Purpose: This study examines the mediating role of psychological safety in the relationship between authentic leadership and innovative work behavior among Generation Z employees in technology companies. Methods: A quantitative survey design was employed, collecting data from 215 Generation Z employees (born 1997–2012) working in Indonesian technology companies through purposive sampling. Structural Equation Modeling with Partial Least Squares (PLS-SEM) was used to test the proposed mediation model. Results: Authentic leadership positively and significantly influenced both psychological safety (β = 0.52, p < 0.001) and innovative work behavior (β = 0.31, p < 0.01). Psychological safety was found to significantly mediate the relationship between authentic leadership and innovative work behavior (indirect effect = 0.22, 95% CI [0.14, 0.31]). Conclusions: Authentic leadership plays a pivotal role in creating an environment where Generation Z employees feel psychologically safe, which in turn encourages them to engage in innovative work behavior. Technology organizations should prioritize authentic leadership development as a strategic lever for sustaining competitive innovation.